Comparison of knowledge about voluntary blood donation among the medical and non-medical students of Universiti Malaysia Sabah - M. Tanveer Hossain Parash; Thiruchelvam Ayudurai; Krishna Dilip Murthy; Sadia Choudhury Shimmi; ABM Tofazzal Hossain; Bablu K Ghosh (Universiti Malaysia Sabah, 2017)
The huge population of persuadable, active, healthy and young students is the potential as blood donors to meet safe blood donation. This study focused on the existing level of knowledge regarding voluntary blood donation among medical (Faculty of Medicine and Health Science) and nonmedical students with science background (Faculty of Engineering) at the Universiti Malaysia Sabah. Four hundred and fifty-five students consisting of medical (231) and nonmedical (224) were selected through stratified random sampling to participate in the study. Data was collected using validated structured questionnaire. Statistical analysis was performed by structural equation modelling using SPSS AMOS Graphics version 22 and SPSS version16. The results showed a significant (p<0.05) difference between the students of medical and nonmedical faculty in their knowledge about voluntary blood donation. The medical and nursing students are more aware about blood donation than the nonmedical students.